Application of Finite Element Analysis Combined With Virtual Computer in Preoperative Planning of Distal Femoral Fracture - He, Yuanming; Liu, Yang; Yin, Bo; Wang, Dong; Wang, Hanzhou; Yao, Peifeng; Zhou, Junlin (Frontiers in Surgery, 2022)
Background: Distal femoral fractures are increasing with an aging population. The computer-assisted preoperative planning has great potential, but there are no preoperative plans to determine appropriate fixation methods for distal femoral fractures on an individual basis. The aims of this study are: (1) to describe the technique of finite element analysis combined with computer-assisted preoperative planning to determine a fixation method for distal femoral fractures and (2) to evaluate the intra-operative realization of this technology and the clinical outcomes based on it for distal femoral fractures. Materials and methods: Between January 2017 and January 2020, 31 patients with distal femoral fractures treated by open reduction and internal fixation were included and randomly divided into 2 groups based on preoperative planning methods: conventional group (n = 15) and computer-assisted group (n = 16). Firstly, how to determine the most appropriate plate and screw length and placement in the preoperative planning of distal femoral fractures was described. The time taken for preoperative planning for different fracture types in the computer-assisted group was then analyzed. Finally, intraoperative and postoperative parameters were compared between the conventional and computer-assisted groups, assessing operative time, intraoperative blood loss, number of intraoperative fluoroscopies, days of hospital stay, Visual Analogue Scale for Pain Score (VAS), and Knee Society Score (KSS). Results: Mean total planning time for 33-A, 33-B, and 33-C fractures in computer-assisted group were 194.8±6.49, 163.71±9.22, and 237±5.33min, respectively. Compared with the conventional group, the patients in the computer-assisted group had less blood loss, fewer fluoroscopic images, and shorter operation time (p<0.05). However, there was no significant difference in the hospitalization days, KSS score and VAS score between the two groups (p>0.05). Conclusions: The results of this study show that the finite element analysis combined with computer-assisted preoperative planning technique can effectively help clinicians to make accurate preoperative planning for distal femoral fractures, especially in the selection of appropriate plate length and screw position.